2008
DOI: 10.1089/scd.2007.0172
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Human Mesenchymal Stem Cells into Dopamine-Producing Cells with Different Differentiation Protocols

Abstract: Several reports have shown that human mesenchymal stem cells (MSCs) are capable of differentiating outside the mesenchymal lineage. We sought to induce MSCs to differentiate into dopamine-producing cells for potential use in autologous transplantation in patients with Parkinson's disease (PD). Following cell culture with various combinations of differentiation agents under serum-free defined conditions, different levels of up-regulation were observed in the protein expression of tyrosine hydroxylase, the rate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 38 publications
0
57
1
Order By: Relevance
“…In this regard, another study demonstrated the importance of factors such as stem cell factor (SCF), produced in situ in the lesioned striatum, to promote the migration and engraftment of MSCs via SCF receptor c-kit (Bantubungi et al, 2008). In the context of PD, several teams, including ours, reported the neuronal differentiation of human MSCs toward a dopaminergic phenotype in vitro, indicating that these cells may constitute an alternative dopamine secreting source of cells (Trzaska & Rameshwar, 2011;Barzilay et al, 2008;Trzaska et al, 2007;). An interesting study also reported no major differences between MSCs from normal patients compared to MSCs isolated from parkinsonian patients, which may be induced to produce up to 30 % of dopaminergic neurons in vitro .…”
Section: Adult Cell Therapymentioning
confidence: 83%
“…In this regard, another study demonstrated the importance of factors such as stem cell factor (SCF), produced in situ in the lesioned striatum, to promote the migration and engraftment of MSCs via SCF receptor c-kit (Bantubungi et al, 2008). In the context of PD, several teams, including ours, reported the neuronal differentiation of human MSCs toward a dopaminergic phenotype in vitro, indicating that these cells may constitute an alternative dopamine secreting source of cells (Trzaska & Rameshwar, 2011;Barzilay et al, 2008;Trzaska et al, 2007;). An interesting study also reported no major differences between MSCs from normal patients compared to MSCs isolated from parkinsonian patients, which may be induced to produce up to 30 % of dopaminergic neurons in vitro .…”
Section: Adult Cell Therapymentioning
confidence: 83%
“…At present, there are a limited number of reports describing dopaminergic neuronal differentiation of MSCs from rodents [24,62,81,216,217] and humans [25,74,81,101,103,214,[218][219][220]. The majority of these studies employed the addition of extrinsic factors to cell cultures, such as cytokines and small molecules; however, the effects of gene transfection, conditioned medium and co-culturing, as well as combinations of these methods were also investigated.…”
Section: Dopaminergic Neuronal Differentiation Of Mscs and Transplantmentioning
confidence: 99%
“…Application of extrinsic factors alone has also resulted in the induction of MSCs toward a dopaminergic neuronal phenotype [25,62,74,103,216,217,219,220]. An NSC-like population was obtained from hMSCs through the formation of neurosphere-like structures in low-attachment culture flasks in the presence of serum-free medium containing EGF and FGF-2 [25].…”
Section: Dopaminergic Neuronal Differentiation Of Mscs and Transplantmentioning
confidence: 99%
See 2 more Smart Citations